Profit and Loss Sharing: Solusi Ekonomi Islam Menghadapi Globalisasi Ekonomi - Faqih Nabhan (IAIN Salatiga, 2010)
This paper aimed at presenting conceptual model that can explain conceptual aplication of profit and loss sharing. Theoritically, Islamic bank, as anintermediary institution, is believed as financial institution helping public economic activities and at the same time carrying out human life. Profit and loss sharing, as one of an Islamic economic mechanism, could be an economic solution of the lack of economics thought. The aplication of profit and loss sharing in budgeting can increase the capability of fund mobilization and investment portofolio without rising of Islamic bank.